Factors affecting cash flow management activities of textile and garment enterprises in Vietnam - Thuy, Linh Vu (Nurture, 2025)
Purpose: This study shows the level of influence of factors on cash flow management activities of enterprises through survey and recovery analysis from data of 50 Vietnamese garment enterprises. Design/Methodology/Approach: The article uses two basic research methods including: qualitative and quantitative research. In which, the qualitative method is to synthesize research works related to the article, thereby determining the research hypothesis. The quantitative method is implemented on the basis of building a scale for 7 factors affecting cash flow management activities and surveyed and analyzed data from 50 textile and garment enterprises in Vietnam to test the published hypotheses. Findings: The results show that 5 out of 7 factors have an impact on cash flow management activities of listed textile and garment enterprises in Vietnam, including: sales policy (SP), inventory management policy (IMP), payment policy with suppliers (PPS), enterprise size (ES) and level of information technology application in cash flow management (LIC). Conclusion: In particular, sales policy is the strongest impact factor, the ability to apply information technology has the weakest impact, in particular, inventory management policy has a negative impact on cash flow management activities. Research Limitations/Implications: From the results of this research, the author suggested for Vietnamese textile and garment enterprises in cash flow management activities. Practical Implications: This research result is completely consistent with previous domestic and foreign studies. Contribution to Literature: The study provides necessary information to help Vietnamese textile and garment enterprises improve cash flow management in the coming time.